Student Responses in Distance Learning at Muslim University Maros and STKIP Paris Barantai Kotabaru - Nirfayanti Nirfayanti; A. Muhajir Nasir (EduMa: Mathematics education learning and teaching, 2022)
During the Covid-19 pandemic, alternative learning solutions were mostly using online. So like it or not, lecturers and students must carry out lectures online. It is true that implementing distance learning is not easy considering that distance learning is a new thing in today's world of education. Nevertheless, Maros Muslim University continues to conduct distance learning in the context of implementing the tridharma of higher education in the form of education and teaching. The research method used in this study is a descriptive method with a quantitative approach that aims to analyze student responses in distance learning using Google Classroom during the Covid-19 pandemic at the Mathematics Education Study Program, FKIP Maros Muslim University. The population and sample in this study were Maros Muslim University students and STKIP Paris Barantai Kotabaru students who took the ICT-Based Learning Design course as many as 41 students who were students of Indonesian Language and Literature Education, and Mathematics Education. The instrument used was a student response questionnaire during distance learning which was made using google form which was analyzed descriptively quantitatively. Based on the results of research and discussion, it was found that most of the student responses indicated that distance learning carried out by lecturers at Maros Muslim University, had been implemented well. This can be seen from the percentage of distance learning indicators that apply at Maros Muslim University, each of which is in the very good and good category or above 90%